PREVENTION OF MADHUMEH AND ITS COMPLICATIONS THROUGH AYURVEDA - Katwal, *Savita; Shrivastava, Akhilesh; Sharma, Dalip (International Journal of Ayurveda and Pharma Research, 2017)
Faulty dietary habits, sedentary life style and stressful conditions may lead to various metabolic disorders and diabetes is one of them. In Ayurveda, Madhumeh one of the types of Vataj prameh is compared to diabetes mellitus because of having similarities of diseases in respect to Etiopathogenesis, clinical features and prognosis. Prevalence of diabetes is increasing day by day throughout the world where India leads the highest numbers. Diabetes is the fourth leading cause of global death by disease. Type-2 DM is    responsible for approximately 90% of cases. The main causes of Madhumeha are lack of exercise, improper food habits, excessive intake of food having Snigdha and Guru guna and food which causes vitiation of Kapha dosha are the primal causes of disease Microvascular complications of diabetes like retinopathy and nephropathy are comparatively lower in Indians. The prevalence of premature coronary artery disease is much higher in Indians compared to other ethnic groups. Diabetic retinopathy is the leading cause of vision loss in adults of working age (20-65yrs) in industrialized countries..Modern therapeutics has many limitations but Ayurvedic principles of management can help the patient to control blood glucose level and have better routine life. Ayurveda plays an important role in prevention of Type-2 DM. Up to 80% of type 2 diabetes is preventable by adopting a healthy diet and increasing physical activity. To prevent this disease and its complications it is necessary to follow principles of Ayurveda i.e. Nidanaparivarjan, Ashtahar Vidhivisheshayatan, Dincharya, Rutucharya, Sadavritta and practicing particular Asana and Yoga postures.